Aseneth of Egypt - Ahearne-Kroll, Patricia D. (The Biblical archaeology review, 2022)
Many know the tale about Joseph, Jacob’s beloved son who was sold into slavery by his jealous brothers, exploited, and imprisoned, but who eventually rose to become second-in-command over Egypt (Genesis 37-50). Buried in this story is a brief reference that fascinated Jewish writers in antiquity: Joseph’s wife, Aseneth, was Egyptian. According to Genesis, […]